Spectrum of cutaneous manifestations in patients with type 2 diabetes mellitus - Roby Bose; Sunil Kumar (Asian Journal of Medical Sciences, 2024)
Background: Skin disorders, usually neglected and frequently under diagnosed among diabetic patients. These are common complications and encounter a broad spectrum of disorders in diabetes. Aims and Objectives: Present study, aimed to evaluate various cutaneous manifestations among type 2 diabetes mellitus (DM) patients. Materials and Methods: The present study was conducted at Dermatology, Diabetic Clinic of tertiary care centre hospital. After approval from the Institutional Ethics Committee and consent from study subjects, 240 subjects were included. All subjects underwent clinical examination-special emphasis on cutaneous manifestations. Blood samples were collected and used for the estimation of blood glucose, liver function tests and renal function tests, complete blood count, bacterial infections-Gram stain and culture, fungal infections-KOH (potassium hydroxide) mount, Gram stain (for Candida), and culture. Results: Out of 200, 140 (58.4%) were males and 100 (41.6%) were females. The majority of the patients were 5th, 6thand 7th decades. Acrochordons 22 (9.1%) and candidal balanoposthitis 21 (8.7%) were predominantly observed. Fungal, bacterial, and non-infective were 90 (37.5%), 54 (22.5%), and 112 (46.6%), respectively. On bacterial culture, Pyogenic ulcer was observed in 8, furunculosis in 6, etc. KOH mount positive in 22 patients and culture positive was seen in 16 patients. In non-infective dermatoses, Acrochordons were observed in 24 patients. The majority of the patients were on oral hypoglycemic agents. Conclusion: This study’s results showed demographic, social factors, and the prevalence of various dermatological manifestations in type 2 DM patients.